2005
DOI: 10.1007/s00213-005-2218-2
|View full text |Cite
|
Sign up to set email alerts
|

Social and environmental influences on opioid sensitivity in rats: importance of an opioid’s relative efficacy at the mu-receptor

Abstract: These findings may be taken as evidence that enriched rats are more sensitive than isolated rats to the effects of lower-efficacy mu-opioids and that social and environmental enrichment leads to functional alterations in opioid receptor populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
32
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 51 publications
(61 reference statements)
8
32
1
1
Order By: Relevance
“…For example, neither methamphetamine-nor morphine-induced CPP is altered reliably by isolation housing (Smith et al, 2005;Thiriet et al, 2011), although one study found that SC mice display greater heroin CPP than EC mice ). In the case of alcohol, isolation housing reliably increases free-access intake in both rats and rhesus monkeys (Kraemer and McKinney, 1985;ProcopioSouza et al, 2011), and similar results are obtained with diazepam (Wolffgramm and Heyne, 1991).…”
Section: Psychosocial Influences and Abused Drugsmentioning
confidence: 99%
“…For example, neither methamphetamine-nor morphine-induced CPP is altered reliably by isolation housing (Smith et al, 2005;Thiriet et al, 2011), although one study found that SC mice display greater heroin CPP than EC mice ). In the case of alcohol, isolation housing reliably increases free-access intake in both rats and rhesus monkeys (Kraemer and McKinney, 1985;ProcopioSouza et al, 2011), and similar results are obtained with diazepam (Wolffgramm and Heyne, 1991).…”
Section: Psychosocial Influences and Abused Drugsmentioning
confidence: 99%
“…For instance, enriched female rats were more sensitive to the aversive effects of the mu opioid morphine in the conditioned taste aversion paradigm [10], and enriched male rats were more sensitive to the rewarding effects of morphine in the conditioned place preference procedure [11]. Similarly, we reported that enriched male rats were more sensitive to the effects of the mixedaction opioids butorphanol and nalbuphine in the conditioned place preference procedure and in a test of thermal antinociception [12]. We also reported that enriched male rats were more sensitive to the effects of the kappa opioid spiradoline on measures of antinociception, diuresis, and conditioned place preference [13].…”
mentioning
confidence: 56%
“…In contrast to these findings, isolated male rats were more sensitive to the effects of morphine on locomotor activity and displayed greater locomotor sensitization following repeated morphine treatment [11]. Furthermore, isolated and enriched male rats did not differ in their oral consumption of morphine in a two-bottle preference test [14], and did not differ in sensitivity to the effects of morphine and levorphanol in a thermal antinociception test [12].Of those studies examining the effects of enrichment on opioid sensitivity, only one has used females [10]. This is a potentially significant issue, given evidence that males and females may respond differently to social and environmental manipulations.…”
mentioning
confidence: 73%
See 2 more Smart Citations